Notch signaling as a master regulator of adult neurogenesis - Lampada, Aikaterini; Taylor, Verdon (Frontiers in Neuroscience, 2023)
Neurogenesis ceases in most regions of the mammalian brain before or shortly after birth, however, in a few restricted brain regions, the production of new neurons proceeds into adulthood. Neural stem cells (NSCs) in these neurogenic zones are integrated into niches that control their activity and fate. Most stem cells in the adult brain are mitotically inactive and these cells can remain quiescent for months or even years. One of the key questions is what are the molecular mechanisms that regulate NSC maintenance and differentiation. Notch signaling has been shown to be a critical regulator of stem cell activity and maintenance in many tissues including in the nervous system. In this mini-review we discuss the roles of Notch signaling and the functions of the different Notch receptors and ligands in regulating neurogenesis in the adult murine brain. We review the functions of Notch signaling components in controlling NSC quiescence and entry into cell cycle and neurogenesis.